2017
DOI: 10.1016/j.ijsu.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs open approach for transverse colon cancer. A systematic review and meta-analysis of short and long term outcomes

Abstract: LPA seems to be safe with equivalent oncological outcomes to OPA and better short term outcomes in selected patient populations. High quality Randomized control trials are required to further investigate the role of laparoscopy in transverse colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…There was no significant difference in IAA rates. Operative time was longer during LA but did not reach statistical significance in the RCT subgroup analysis [141].…”
Section: Q23: What Is the Best Non-operative Management Of Patientsmentioning
confidence: 74%
“…There was no significant difference in IAA rates. Operative time was longer during LA but did not reach statistical significance in the RCT subgroup analysis [141].…”
Section: Q23: What Is the Best Non-operative Management Of Patientsmentioning
confidence: 74%
“…From these results we can conclude that a laparoscopically-assisted operation for colon adenocarcinoma is comparable to open operation from the oncological point of view. Other authors reported different findings; some authors found no connection between recurrence rate and type of operation [22,23]. Ringressi et al found higher association between recurrence rate and open surgery [12].…”
Section: Discussionmentioning
confidence: 97%
“…In the treatment of colorectal cancer, laparoscopic surgery has developed rapidly throughout the world due to advantages such as smaller incision, less pain, reduced intraoperative blood loss, faster recovery, and shorter hospitalization compared with open surgery [ 5 7 ]. These clinical benefits of laparoscopic surgery for colorectal cancer have been proved by a series of a large sample, multicenter, randomized controlled trials [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%